(untitled) (Journal of Scientific Research, 2024)
Thin films of composite Zinc Tin Oxide (ZTO) are grown on glass substrates by thermal vapor evaporation. Thin films with different ratios of ZnO: SnO2= (90:10, 80:20, 70:30, 60:40 and 50:50) wt% were prepared and annealed at 500 °C for 2 h. The X-ray diffraction (XRD) patterns reveal that the ZTO films have become polycrystalline as we increase the percentage of tin oxide. The crystallinity of films also increases significantly. The field emission scanning electron microscopy (FESEM) results indicate that the percentage of tin oxide changes the film’s morphology. UV visible spectroscopy of the films indicates that the band gap is reduced with the increased percentage of tin oxide in the mixture, and transmittance is also decreased at a higher percentage. The transmittance of the films ranges from 90 to 83 %, while the band gap falls within the range of 3.90 to 3.40 eV. These characteristics make the films well-suited for solar cell window layers.